Targeting VCAM-1: a therapeutic opportunity for vascular damage. (4th March 2023) - Troncoso, Mayarling F; Díaz-Vesga, Magda C; Sanhueza-Olivares, Fernanda; Riquelme, Jaime A; Müller, Marioly; Garrido, Luis; Gabrielli, Luigi; Chiong, Mario; Corbalan, Ramon; Castro, Pablo F; Lavandero, Sergio
ABSTRACT: Introduction: The vascular cell adhesion molecule (VCAM-1) is a transmembrane sialoglycoprotein detected in activated endothelial and vascular smooth muscle cells involved in the adhesion and transmigration of inflammatory cells into damaged tissue. Widely used as a pro-inflammatory marker, its potential role as a targeting molecule has not been thoroughly explored. Areas covered: We discuss the current evidence supporting the potential targeting of VCAM-1 in atherosclerosis, diabetes, hypertension and ischemia/reperfusion injury. Expert opinion: There is emerging evidence that VCAM-1 is more than a biomarker and may be a promising therapeutic target for vascular diseases. While there are neutralizing antibodies that allow preclinical research, the development of pharmacological tools to activate or inhibit this protein are required to thoroughly assess its therapeutic potential.